Combining Flipped Classroom and Mind Mapping in Indonesian Vocational Schools: Their Influence to Students’ Critical Thinking Ability - Nugroho, Roni Agung; Basori, Basori; Maryono, Dwi (IJIE (Indonesian Journal of Informatics Education), 2020)
The main problem of students in solving problems is the low ability to think. This study aims to improve students' critical thinking skills and measure the effectiveness of the combination of flipped classroom learning models and mind mapping. This research method used is a quantitative approach with a quasi-experimental design. The sample from this study was 31 students from the experiment class and 31 students from the control class. Data collection is done through critical thinking tests. Before using multiple-choice pre-tests and post-tests, instruments are tested first using validity tests and reliability tests. The results showed that the critical thinking abilities of students in the experiment class through the combined learning of flipped classroom models and mind mapping were higher than the control class, interpreted from the post-test score of the experiment class 77.6 while the control class got a score of 71.4. From the effectiveness of the experiment, class learning also got a score gain of 40.4947 with a fairly effective category, while the control class gained a score gain of 38.0115 with ineffective categories.